2022
DOI: 10.3390/healthcare10030575
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Custom Foot Insoles to Decrease Plantar Pressure: A Cross-over Randomized Trial Study

Abstract: Background: Harderness insoles decrease plantar pressure and reduce the foot injury incidence in sport. The purpose of our study was to analyze the plantar pressure variation in moto riders after riding in a real speed circuit with a custom foot 520 Shore EVA insole. Methods: A crossover randomized trial study was performed (consent no. #050520165316). Riders were assessed by an expert motorsport senior podiatry. The participants’ mean age was 35 ± 3.29. Participants completed a 20 min training riding with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Casado et al [36,37] analyzed the variation in the plantar pressure with hardness using noncontoured insoles made with polypropylene and aluminum in the metatarsal head and EVA 52 • Shore A in motorcycle sport and concluded that the plantar pressure generated by the rider on a motorcycling simulator decreased using hard insoles. Taking into consideration the similarity in the insoles used, in our research, the plantar pressure was preceded by a cycling movement of foot-shoe-pedal, in contrast to the motorcycle that only used a support movement, but nevertheless, in both situations using similar insoles, in all cases, the plantar pressure decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Casado et al [36,37] analyzed the variation in the plantar pressure with hardness using noncontoured insoles made with polypropylene and aluminum in the metatarsal head and EVA 52 • Shore A in motorcycle sport and concluded that the plantar pressure generated by the rider on a motorcycling simulator decreased using hard insoles. Taking into consideration the similarity in the insoles used, in our research, the plantar pressure was preceded by a cycling movement of foot-shoe-pedal, in contrast to the motorcycle that only used a support movement, but nevertheless, in both situations using similar insoles, in all cases, the plantar pressure decreased.…”
Section: Discussionmentioning
confidence: 99%